Entrepreneurial Mentoring Synergy: An In-Depth Analysis of Polytechnic and Community College (PolyCC) Lecturers as Mentors to Student Start-Up Entrepreneurs - Hariyaty binti Ab Wahid (Tanjung Malim, 2024)
Entrepreneurial Mentoring Synergy: An In-Depth Analysis of Polytechnic and Community College (PolyCC) Lecturers as Mentors to Student Start-Up Entrepreneurs by Hariyaty binti Ab Wahid